2020
DOI: 10.20377/jfr-372
|View full text |Cite
|
Sign up to set email alerts
|

His and her working hours and well-Being in Germany: A longitudinal crossover-spillover analysis

Abstract: This paper investigates the relationship between work time arrangements and personal well-being in married and cohabiting couples. Using data from the German Socio-Economic Panel Survey (SOEP), we study how the number of hours worked by the survey respondents and their partners influenced their own well-being. We also investigate possible transmission mechanisms between the two variables, namely income, hours spent in homemaking and care activities, and possible mismatch between desired and actual hours. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Three models are presented: an unadjusted model, a model adjusted for covariates but without baseline work hours, and a fully adjusted model. We also conducted a sensitivity analysis to test the potential ‘actor-partner’ effects [ 17 , 18 ] in the association between unpaid care work hours (housework and childcare) and psychological distress amongst couples, that is to investigate whether partner’s housework and childcare hours were related to the individual’s distress in addition to their own. To test this ‘actor-partner’ effect, we limited the sample to couples and included partner’s and actor’s hours of housework or childcare in the model as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three models are presented: an unadjusted model, a model adjusted for covariates but without baseline work hours, and a fully adjusted model. We also conducted a sensitivity analysis to test the potential ‘actor-partner’ effects [ 17 , 18 ] in the association between unpaid care work hours (housework and childcare) and psychological distress amongst couples, that is to investigate whether partner’s housework and childcare hours were related to the individual’s distress in addition to their own. To test this ‘actor-partner’ effect, we limited the sample to couples and included partner’s and actor’s hours of housework or childcare in the model as well.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, previous research on family and well-being has suggested the crossover effects of the partner, that is one’s well-being may not only depend on one’s own but also on their partners’ involvement in work and family [ 17 , 18 ]. Perceptions of equality and reciprocity within couples are likely to be important [ 13 , 19 ], so how couples divide the unpaid care work and how they make an adjustment on paid work due to unpaid care may contribute to couples’ perceptions of equity (or inequity) in a relationship, and thus potentially influence health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Given the declining fertility rate and the high number of women working part-time in Germany, it is also important to investigate employment variations among dual-earner couples to better understand this relationship within the German context. As prior work suggests, despite the introduction of more progressive family policies in recent years, Germany is still marked by traditional gender ideologies (Florean & Engelhardt, 2020;Geist & Brauner-Otto, 2017;Konig & Cesinger, 2015) and a legacy of policies that promote the married, male breadwinner ideal (Fleckenstein & Seeleib-Kaiser, 2011;Klammer & Letablier, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus a subjective given and cannot be objecti ed, since "this blinds us to the subjective interpretation of the state of affairs of the person" (Antonovsky, 1979, p. 36). In western societies, however, both personal as work factors are considered to have a signi cant effect on the well-being (Florean & Engelhardt, 2020;Fukasawa et al, 2020) Prior studies suggest that health-related disasters are associated with a decline in well-being (Sprang & Silman, 2013). Yet current studies are fragmented as different groups within society are impacted in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Quite a lot of, also more specialized, attention has gone to health care workers, offering rst line help to infected people, even while knowingly putting themselves at risk (Evanoff et al, 2020). Other studies focus on the well-being of social workers (Berg-Weger & Morley, 2020;Florean & Engelhardt, 2020;Miller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%